The role of institutional conditions in the impact of economic growth on poverty - Saeedeh Behnezhad; Mohammad Javad Razmi; Saeed Malek Sadati (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2021)
Purpose: According to the New Institutional View, the main reason for the great difference between countries in terms of growth, development and economic welfare is their institutional structures and foundations. Creating a stable structure in human relationships, institutions reduce insecurity, transaction costs and increase people's motivation. In this regard, the present study examined the role of institutional conditions in the impact of economic growth on poverty in middle and high per capita income countries from 2004 to 2017. Design/methodology/approach: This study was conducted by the panel threshold approach and the general index of good governance was used to measure the institutional quality, calculated using the weighted average of the six governance indices of the World Bank. Findings: The threshold value in this model is -1.0583, indicating that when the good governance index crosses this threshold and the institutional quality improves, economic growth will reduce poverty to a greater extent. Research limitations/implications: In this study, we faced data limitations on poverty, and many countries did not have continuous annual data. Originality/value: To my knowledge, no study has been conducted yet on the role of institutional quality in the impact of economic growth on poverty. Therefore, this study enhances our understanding of the importance of institutions and their effect on the relationship between economic growth and poverty.
Keywords: C24; O40; E02; I32; 330; Economic Growth; Institutional Conditions Panel Threshold; Poverty